180 Mindfulness-based intervention in patients with persistent pain in chest (mipic) of non-cardiac cause: a feasibility randomised-control study. (6th June 2022) - Mittal, Tarun; Evans, Emma; Pottle, Alison; Lambropoulos, Costas; Morris, Charlotte; Surawy, Christina; Chuter, Antony; Cox, Felicia; deSilva, Ranil; Mason, Mark; Banya, Winston; Thakrar, Diviash; et al.
Abstract : Introduction: Stable chest pain is a common symptom in clinical practice and obstructive coronary artery disease as the underlying cause is found only in 10% of patients presenting to rapid access chest pain clinics. Mindfulness, which is a well-recognised method to reduce stress and anxiety, has also been used to manage chronic pain but its use in chest pain has not been described.METHODS: We carried out a prospective 2:1 randomised controlled trial comparing the intervention of adapted Mindfulness-Based Cognitive Therapy (MBCT) as an addition to usual care with just usual care in controls. 573 patients aged 18–75 years attending the rapid access chest pain clinic over the last 12-months who had persistent chest pain but no diagnosed cardiac cause were evaluated for eligibility. The intervention was a 2-hour, weekly, online guided 8-week MBCT course. Compliance with attendance and the home practice was recorded. Enrolled patients completed the Seattle angina questionnaire (SAQ), Hospital Anxiety and Depression Scale, Cardiac Anxiety Questionnaire, Five-facet Mindfulness Questionnaire, and EQ-5D-5L at baseline assessment and after 8-week period. RESULTS: 418 patients (72.9%) fulfilled the eligibility criteria, of whom persistent chest pain was reported by 114 patients (32%) out of 356 patients who could be contacted. Of these, 33 (29%) patients with a mean age of 54.2 (±12.2) years and 68% women, consented to the study. Baseline questionnaires revealed mild physical limitation (mean SAQ, 76.8 ±25), high levels of anxiety (76%) and depression (53%), modest cardiac anxiety (CAQ, 1.78±0.61) and mindfulness score (FFMQ, 44.9±7.2). 6 patients subsequently withdrew due to bereavement, caring responsibilities, and ill-health. Of the remaining 27 participants, 18 in the intervention arm attended an average of 5 sessions with 61% attending ≥6 sessions. Although not statistically powered, the study revealed a significant reduction in general anxiety, improved mindfulness, and a trend towards improvement in SAQ scores in the intervention arm. CONCLUSION: One-third of patients with persistent non-cardiac chest pain were willing to participate in mindfulness-based therapy. An improvement in anxiety and mindfulness was detected in this feasibility study. A larger trial is required to demonstrate improvement in chest pain symptoms.IMPLICATIONS: As chest pain continues to persist in one-third of patients without a cardiac cause alongside associated anxiety and depression, mindfulness-based interventions may be a useful alternative that empowers patients, reduce dependence upon analgesics and opioids, and reduce attendance to GPs and hospitals. However, the efficacy of such therapies in reducing chest pain has to be explored in a larger study. Conflict of Interest: NONE